TRANSGRESSION OF LEGAL TEXT IN LATE JOSEON KOREA – FOCUSING ON "HEUMHEUMSINSEO" – - KANG, Hyejong (International Journal of Korean Humanities and Social Sciences, 2020)
This article aims to shed light on the transgression of legal text in Late Joseon Korea. Legal text of Joseon contains ‘self-confession’ that reveals the cracks of yechi 예치 禮治, dominance under the Confucian norm. In this regard, this article reviews the principles of penal administration and legal culture in late Joseon period which functioned as the mechanism to produce dominant discourses to control transgressions. In particular, focusing on Heumheumsinseo 흠흠신서 欽欽新書 written by Jeong Yakyong 정약용 丁若鏞 (1762-1836), which contains most diverse types of legal texts, this article takes the transgression of genre of legal texts into consideration. Through this, how the secular genre of legal text obtains the cultural reality and reveals the suppressed social discourse would be explained.